Situation of tobacco use and health effects among employees who working in bank in centrel of denizli - Meydan Acımış, Nurhan; Bostancı, Mehmet; Bozkurt, Ali İhsan and Özşahin, Aysun (Journal of Dependence, 2008)
Objective: The Banks are financial institutions and foundations which have very important place in all over the world and in our country due to banking services and their contributions on the trade- life. This study is done among members of staff working at the banks in Denizli in the aim of showing staff’s, how often they tobaco uses, effecting agents and health effects. Method: A cross sectional study was planned. This study includes 654 staff working at the banks in the city centre of Denizli with the rest of this number which 31 bank approved this study couldn’t have been got through . All data obtained in this investigation were collected by the techniques of questionnaires. Chi-square statistics analysis was used to evaluate datas. Results: 654 bank staff members were participated in this study. Among being got through to members of staff , % 58,9 are males(384), and % 41.01 are females (267). %84.0 of staff members working at banks has given about smoke cigarette condiction %67.9(369) of members of staff working at banks are smokers and %32.9(181) aren’t smoke(p>0.05). %73.4 of staff members working at banks has been smoked cigarette between 1-10 years experienced(p<0.05) .Respiratory tract diseases most health problems among them during were claimed ever in the last one year(p<0.05). Conclusion: Using tobacco very widespread dependence in our country . For tobacco control such a bank institutions and foundations which have been worked indoor place servises, 4207 number law rullers should done with determination. Dependence prevention efforts could be be-nefical among bank staff member.